2008
DOI: 10.1167/iovs.07-1206
|View full text |Cite
|
Sign up to set email alerts
|

The Angiopoietin/Tie-2 System Regulates Pericyte Survival and Recruitment in Diabetic Retinopathy

Abstract: These findings demonstrate that Tie-2 is functional in pericytes and may play an important role in the progression of diabetic retinopathy, by regulating pericyte loss and influencing the activation state and recruitment of pericytes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
116
1
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 143 publications
(125 citation statements)
references
References 46 publications
5
116
1
3
Order By: Relevance
“…Overexpression of Ang1, on the other hand, leads to a stabilized vasculature (39)(40)(41)(42)(43)(44). Also, treatment with recombinant Ang1 has been shown to rescue retinal defects caused by pericyte loss (39,46). Here we report that DA can induce overexpression of Ang1 directly in the pericytes and also can regulate the mobilization and recruitment of these cells, in turn mediating normalization of tumor blood vessels.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…Overexpression of Ang1, on the other hand, leads to a stabilized vasculature (39)(40)(41)(42)(43)(44). Also, treatment with recombinant Ang1 has been shown to rescue retinal defects caused by pericyte loss (39,46). Here we report that DA can induce overexpression of Ang1 directly in the pericytes and also can regulate the mobilization and recruitment of these cells, in turn mediating normalization of tumor blood vessels.…”
Section: Discussionmentioning
confidence: 71%
“…In addition, these experiments performed in serum-starved HBVP suggested that the effect of DA on Ang1 expression in pericytes is direct and is not the result of its actions on other growth factors. Furthermore, because there are reports indicating that up-regulation of Ang1 in pericytes stimulates migration of these cells (46,47), we examined the action of DA on HBVP migration (SI Results and Fig. S6).…”
Section: Da Treatment Promotes Mature Pericyte Coverage In Tumor Bloodmentioning
confidence: 99%
“…Other angiogenic factors are the angiopoietin/Tie-2 system which, as mentioned earlier, modulates the effect of VEGF on endothelial cells (Takagi et al 2003;Cai et al 2008). Several cytokines also have been shown to have a role in new vessel formation in PDR such as insulinlike growth factor-1 (IGF-1), interleukin-8, placental growth factor, hepatocyte growth factor, platelet-derived growth factor (PDGF), and leptin (Simo et al 2006).…”
Section: Angiogenic Mechanisms In Proliferative Diabetic Retinopathymentioning
confidence: 98%
“…Both angiopoietins interact with a tyrosine kinase receptor called Tie-2 receptor (Suri et al 1996;Maisonpierre et al 1997). The angiopoietin/Tie-2 system has an important role in the pathogenesis of proliferative diabetic retinopathy (Takagi et al 2003;Cai et al 2008).…”
Section: Key Angiogenic Growth Factors Involved In Proliferative Retimentioning
confidence: 99%
“…In addition, paracrine signalling from ECs recruits pericytes by the secretion of platelet derived growth factor (PDGF)-BB, which binds to the PDGFRβ receptor expressed on pericytes (Bjarnegard et al, 2004). In addition, the secretion of angiopoietin 1 (Ang-1) by pericytes mediates pericyte-endothelial attachment via the Tie2 receptor, which is expressed by ECs (Cai et al, 2008;Sundberg et al, 2002). Disruptions in pericyte-endothelial interactions can result in the loss of pericyte coverage from the vessels and lead to a leaky vasculature, resulting in haemorrhage and oedema (Hellstrom et al, 1999;Soriano, 1994).…”
Section: Bone Marrow-derived Mesenchymal Stem Cells and Pericytes -Dementioning
confidence: 99%